1990
DOI: 10.1088/0952-4746/10/3/306
|View full text |Cite
|
Sign up to set email alerts
|

Radiation research priorities in the mineral sands industry

Abstract: Mineral sands processing involves exposure to external and internal radiation sources. The level of exposure is associated with the production of monazite, which contains approximately 6% thorium by weight. External radiation levels may range from less than 1 µGy h-1 to 10 µGy h-1 in the general plant environment, to greater than 150 µGy h-1 in monazite storage areas. Internal radiation may also be significant since airborne gross alpha activity levels from less than 0.05 Bq m-3 to about 5 Bq m-3 are found. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…According to ARPANSA (2014); Hewson (1990); IAEA (2006); Koperski (1993) the radiation hazard in the production of mineral sands arises from:…”
Section: Sources Of Exposure To Nors In the Wa Msimentioning
confidence: 99%
See 4 more Smart Citations
“…According to ARPANSA (2014); Hewson (1990); IAEA (2006); Koperski (1993) the radiation hazard in the production of mineral sands arises from:…”
Section: Sources Of Exposure To Nors In the Wa Msimentioning
confidence: 99%
“…The significance of the potential exposures to workers in the MSI were highlighted by Hewson (1990) who reported that in 1987 the maximum potential dose to a worker was approximately 165 mSv, in excess of three times the annual effective dose limit. Inhalation of LLα contributed ∼90% of the dose; γ contributed ∼10% whilst the contribution from TnP and RnP was negligible.…”
Section: Sources Of Exposure To Nors In the Wa Msimentioning
confidence: 99%
See 3 more Smart Citations